2017
DOI: 10.1016/j.envint.2017.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Airborne particles in indoor environment of homes, schools, offices and aged care facilities: The main routes of exposure

Abstract: It has been shown that the exposure to airborne particulate matter is one of the most significant environmental risks people face. Since indoor environment is where people spend the majority of time, in order to protect against this risk, the origin of the particles needs to be understood: do they come from indoor, outdoor sources or both? Further, this question needs to be answered separately for each of the PM mass/number size fractions, as they originate from different sources. Numerous studies have been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
146
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(153 citation statements)
references
References 56 publications
2
146
2
3
Order By: Relevance
“…This section is intended to review the general influence of factors on the airborne transmission indoors. However, it should be noted that different types of indoor environment (eg, residential buildings, office buildings, schools, hospitals, and aircraft cabins) could have very distinctive issues and characteristics of airborne transmission, basically because of their different geometries and layouts of indoor spaces, air distribution methods, supply flow rates, occupant densities, occupants’ behaviors, etc . For example, residential buildings do not have a fixed layout of occupants and they are mostly naturally ventilated when the outdoor air temperature is acceptable.…”
Section: Current Understanding Of Airborne Transmission Indoorsmentioning
confidence: 99%
“…This section is intended to review the general influence of factors on the airborne transmission indoors. However, it should be noted that different types of indoor environment (eg, residential buildings, office buildings, schools, hospitals, and aircraft cabins) could have very distinctive issues and characteristics of airborne transmission, basically because of their different geometries and layouts of indoor spaces, air distribution methods, supply flow rates, occupant densities, occupants’ behaviors, etc . For example, residential buildings do not have a fixed layout of occupants and they are mostly naturally ventilated when the outdoor air temperature is acceptable.…”
Section: Current Understanding Of Airborne Transmission Indoorsmentioning
confidence: 99%
“…A recent literature review by Morawska et al has summed up the UFP levels measured outdoors and indoors in houses, offices, schools, and day‐care centers, measured by international studies. Only one recent literature review regarding child exposure was found .…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in rural environments showed a higher indoor UFP concentration (Figure ). In the review by Morawska et al, in which the UFP exposure levels found in different studies were weighted and expressed as mean exposure levels, these were higher indoors than outdoors (1.44·10 4 and 1.31·10 4 part/cm 3 , respectively). This is probably due to the fact that in these environments there are fewer outdoor UFP sources compared with urban or suburban areas .…”
Section: Discussionmentioning
confidence: 99%
“…Indoor air pollution is a serious health problem as it causes about 4.5 million annual deaths globally resulting from pneumonia (12%), stroke (34%), ischemic heart diseases (IHD) (26%), chronic obstructive pulmonary diseases (COPD) (22%), and lung cancer (LC) (6%) (Amoatey et al, 2017;Tageldin et al, 2012;Thurston et al, 2016;WHO, 2018). Indoor air pollution has been extensively studied in homes (Morawska et al, 2017;Rohra and Taneja, 2016), schools (Cai et al, 2015;Forns et al, 2017), hospitals (Cabo Verde et al, 2015;Wang et al, 2015b), offices (Azuma et al, 2018;Song et al, 2015), restaurants (Dai et al, 2018;Fazlzadeh et al, 2015), and subway metros (Kim et al, 2015;Xu and Hao, 2017). However, indoor air pollution continues to be a global problem, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…These indoor air pollutants generally originate from the ambient environment. However, in cities with high ambient air pollutant levels, indoor air pollutants may be of greater concern (Morawska et al, 2017).…”
Section: Introductionmentioning
confidence: 99%